Beyond Woodlands: Legal Ableism and the Post-Institutional Dialogue - McKelvie, SH (Critical Disability Discourses, 2016)
The Woodlands class action suit and settlement of 2009, which addressed the systemic abuse that many survivors experienced while institutionalized, is a complex moment in the legal histories of BC. The settlement and ongoing struggles for adequate provincial restitution have raised concerns regarding medico-legal conceptualizations of developmental and intellectual (dis)abilities. Using the conceptual frameworks of critical legal theory, critical disability studies, and feminist methodologies, this study draws upon three interviews with community members, discussing their insights into the history of the Woodlands school, the class action suit and the settlement process. The interviews provide alternative accounts of tort litigation within the provincial system of care. This paper examines bio-political discourses regarding ‘mental capacity,’ embedded in exchanges that take place at the everyday, legislative, and judicial levels that affect people with (dis)abilities. Practices of self-advocacy and service provision are complicated by past asylum knowledges and by the ontological hegemony of neoliberal polities of today. For the informants, the conditions of justice resulting from the Woodlands case remain indeterminate, inviting further investigations into anti-institutional narratives and diverse responses to ‘legal ableism.’ Le recours collectif et l’entente de Woodlands de 2009 qui traitaient des abus systématiques vécus par de nombreux survivants alors qu’ils étaient institutionnalisés, représente un moment complexe de l'histoire juridique de la Colombie-Britannique. L’entente et les luttes ininterrompues pour une restitution adéquate ont soulevé des questions concernant les conceptualisations médico-légales des handicaps intellectuels et du développement. En utilisant des concepts provenant de la théorie juridique critique, des études critiques dans le champ de l'incapacités, et des études féministes, cet article tente d'analyser les résultats de trois entretiens qui ont eu lieu avec des membres de la communauté afin de discuter leur regard sur l’histoire de Woodlands, du recours collectif et du processus pour arriver à une entente. Les entretiens représentent des récits alternatifs du litige civile au sein du système des soins. Le présent article examine les discours biopolitiques concernant ‘la capacité mentale’ qui sont enchâssés dans les échanges quotidiens qui ont lieu au niveau juridique et législatif, et qui affectent les personnes ayant des (in)capacités. Les activités de l'auto-défense et de l’approvisionnement des services sont compliqués par le savoir des asiles du passé et par l'hégémonie ontologique des régimes politiques néolibéraux actuels. Pour les informateurs, les conditions de justice résultant du cas de Woodlands reste indéterminées. L’invitation est lancée pour d’autres recherches sur les récits anti-institutionnels et les réponses possibles au capacitisme juridique.